Actualization of pre-service training for prospective biology teachers to improve mastery of pedagogical and content knowledge (PCK) - Lubis, Silvi Puspa Widya; Muzana, Syarifah Rahmiza; Meutia, Putri Dini; Yanto, Bagus Endri (Biosfer: Jurnal Pendidikan Biologi, 2025)
Preservice teachers must have a good understanding of Pedagogical and Content Knowledge (PCK) to improve their performance in science teaching. This study aims to evaluate the effect of preservice training for preservice Biology teachers on improving PCK understanding. The research method used is one group pre-test post-test design with a quantitative approach. The population of this research is Biology Education Department students of the teacher training and Education Faculty, while the sample consisted of 30 students selected using purposive sampling. The instrument used was a test, to determine the mastery of Pedagogical Content Knowledge (PCK). The test instrument in the form of descriptive test questions (pre-test and post-test) is used to determine the mastery of Pedagogical Content Knowledge (PCK) skills of prospective teachers before and after learning. Data were analyzed using paired sample t-tests and quantitative descriptive analysis. The result showed that students’ post-test scores for content knowledge and pedagogy were higher than the pre-test. In conclusion, the implementation of pre-service training for prospective Biology teachers significantly improves their understanding of PCK. Therefore, this pre-service training is essential to develop PCK that can be used in designing learning experiences that follow specific pedagogy and content.